Human Capital and University-Industry Linkages' Role in Fostering Firm Innovation : An Empirical Study of Chile and Colombia - Marotta, Daniela (World Bank, Washington, DC, 2012)
A firm's absorptive capacity, human capital and linkages with knowledge institutions have been shown to increase the firm's probability of innovating in OECD economies. Despite its importance for national- and firm-level competitiveness, few papers examine the impact of the same variables for firms innovation in Latin America. This paper investigates the link between firm innovation and its absorption capacity as proxied by the presence of a R&D department, the firm's human capital, and its interaction with research centers and universities. We analyze the case of Chilean and Colombian manufacturing firms using data from innovation surveys. A probit regression model is applied to identify the determinants of innovation activity. We find that collaboration with university and research institutions is associated with an increase in the probability of introducing a new product in Chilean and Colombian firms of 29 and 44 percent, respectively, and it can increase up to 58 percent in the case of Colombian firms interacting with research centers. Moreover, firms whose employees have a higher level of education, or whose managers/supervisors have a higher (perceived) level of knowledge, are more likely to innovate. Although the estimates could be affected by biases and suffer from shortcomings in data, the findings suggest that policies and incentives to increase firm-level human capital and industry-university linkages are important to increase innovation in Latin America.